Detection of vegetation coverage changes in the Yellow River Basin from 2003 to 2020 - Liu, Chenxi; Zhang, Xiaodong; Wang, Tong; Chen, Guanzhou; Zhu, Kun; Wang, Qing; Wang, Jing (Ecological indicators, 2022)
•From 2003 to 2020, Fractional Vegetation Cover (FVC) increased at a rate of 0.19•Due to the differences in topography and landforms, the FVC in the Yellow River Basin presents obvious spatial differences.•FVC in 73% of the basin shows high stability.•There is obvious seasonal characteristics of FVC in the basin. The Yellow River occupies a pivotal strategic position in the development and economic construction of China. Moreover, grasping the dynamics of change in long-term vegetation cover and predicting future trends in the Yellow River Basin could provide an empirical foundation for improved ecological protection and soil and water conservation initiatives. This study uses statistical methods such as Dimidiate pixel model, linear regression, Moran’s index, and coefficient of variation to conduct a spatio-temporal analysis of the vegetation coverage in the Yellow River Basin. The Hurst exponent is used for further analysis of the trend of change in the vegetation coverage across the study area. The results show that from 2003 to 2020, the fractional vegetation coverage (FVC) in the Yellow River Basin increased at an average rate of 0.19% per year. Furthermore, only 2.22% of the area of the Yellow River Basin shows a relative increase in FVC from 2003 to 2020; most of the increased area is located in the northwestern Loess Plateau. The Global Moran index values from 2003 to 2020 are all greater than 0.8, indicating that the vegetation coverage presents a strong agglomeration. According to the Local Moran index, the vegetation coverage of the Yellow River Basin presents a strong spatial difference. According to the coefficient of variation, 73% of the vegetation coverage in the Yellow River Basin has been highly stable over the past 18 years. In addition, the overall Hurst exponent for the FVC in the Yellow River Basin is less than 0.5, indicating a anti-persistence pattern of change in vegetation.